New intragenic and promoter region deletion mutations in FERMT1 underscore genetic homogeneity in Kindler syndrome. (1st April 2014) - Fuchs‐Telem, D.; Nousbeck, J.; Singer, A.; McGrath, J. A.; Sarig, O.; Sprecher, E.
Summary: Background: Kindler syndrome (KS) is a rare autosomal recessive skin disorder, which was recently reclassified as a subtype of epidermolysis bullosa. Despite the fact that loss‐of‐function mutations in the FERMT1 gene, encoding kindlin‐1, have been shown to cause the syndrome in numerous patients, a small number of typical cases of KS in which FERMT1 mutations could not be identified has raised the possibility that the disorder may be genetically heterogeneous. Aim: To assess two highly consanguineous families with clinical characteristics of KS. Results: In the first family, a hitherto unreported deletion (c.137–140delTAGT) in FERMT1 was detected, which is predicted to lead to premature termination of translation. However, direct sequencing of the coding region of FERMT1 failed to disclose any pathogenic change in the second family. To confirm the possibility that the disease in this family may be due to a mutation in another gene, we used homozygosity mapping, and found that all affected family members share a segment of homozygosity on 20p12.3, spanning the FERMT1 gene. Accordingly, a large and highly unusual deletion (g.‐711‐1241del) spanning the putative FERMT1 promoter sequence and the first noncoding exon of the gene was found to cosegregate with the disease phenotype in this family, and to prevent transcription of the gene, as attested by the lack of FERMT1 message in the skin of a patient. Conclusion: The present data provide evidence in support of genetic homogeneity in KS.